AB0300 ACPA in Reduction of BMD in Premenopausal RA Patients. (10th June 2014) - Helal, A.-M.H.; El Kaffash, D.; Shahen, E.; Hassan, M.; Abdel-Fattah, Y.H.
Abstract : Background: Bone strength depends on its structure, the material properties, and bone turnover; bone mineral density (BMD) loss results in micro-architectural deterioration and decreased mechanical strength of bone. In rheumatoid arthritis (RA), this loss occurs in two forms; generalized BMD loss with axial distribution, and peri-articular (localized) BMD loss, extra-articular bone loss seen in the proximity of the inflamed joints. Anti-cyclic-citrullinated peptide antibodies (ACPA) are highly specific for RA, where degree of ACPA positivity has been identified as an important initiator of skeletal damage. Objectives: The aim of this work was to assess bone loss in ACPA positive and ACPA negative premenopausal RA patients, and serum β- Cross Laps as a bone marker. Methods: Fifty six RA patients diagnosed according to 2010 ACR/EULAR criteria (40 ACPA positive 39±7 years and 16 ACPA negative 43±6 years) and 35 healthy premenopausal females 40±7 years were included in this study. Disease activity and disability was scored by disease activity score 28 (DAS 28) and Health Assessment Questionnaire (HAQ) respectively. Bone mineral density (BMD) of femoral neck, spine, and distal forearm was measured by dual energy X ray absorptiometry (DXA) and bone turnover was measured by serum β- Cross Laps. Results: BMD in the spine (p=0.001), femur (p=0.001) and distal forearm (p=0.001) was markedly lower in ACPA positive patients compared to ACPA negative and control groups. ACPA positive patients also showed a higher rate of bone turnover assessed by β- Cross Laps (p=0.013) than the ACPA negative and control group. The ACPA positive patients showed higher disease activity (p=0.012) and disability than the ACPA negative patients (p=0.009). There was a statistically significant correlation between bone loss in the spine and both disease activity and disability (p=0.042 & p=0.012 respectively). Conclusions: ACPA positive RA patients has a higher rate of bone loss and turnover, as well as higher disease activity and disability scores compared to the ACPA negative patients and control group. There is also a positive correlation between bone loss and both disease activity and disability in ACPA positive patients. References: Kocijan R, Harre U, Schett G. ACPA and bone loss in rheumatoid arthritis. Curr Rheumatol 2013;15(10):366. Guler-Yuksel M, Allaart CF, Goekoop-Ruiterman Y, de Vries-Bouwstra JK, van Groenendael J, Mallee C, et al. Changes in hand and generalized bone mineral density in patients with recent-onset rheumatoid arthritis. Ann Rheum Dis 2009;68:330-6. Schett G, Kiechl S, Weger S, et al. High-sensitivity C-reactive protein and risk of nontraumatic fractures in the Bruneck study. Arch Intern Med 2006;166:2495–2501. Acknowledgements: DXA and Bone markers where done in and founded by The Regional Women Health Institute. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1268